Applying a Behavioral Model Framework for Disaster Recovery Research in Local Public Health Agencies: A Conceptual Approach. (27th April 2015) - Walsh, Lauren; Garrity, Stephanie; Rutkow, Lainie; Thompson, Carol B.; Strauss-Riggs, Kandra; Altman, Brian A.; Schor, Kenneth; Barnett, Daniel J.
Abstract: The local public health agency (LPHA) workforce is at the center of the public health emergency preparedness system and is integral to locally driven disaster recovery efforts. Throughout the disaster recovery period, LPHAs have a primary responsibility for community health and are responsible for a large number of health services. In the face of decreasing preparedness funding and increasing frequency and severity of disasters, LPHAs continue to provide essential disaster life cycle services to their communities. However, little is known about the confidence that LPHA workers have in performing disaster recovery-related duties. To date, there is no widely used instrument to measure LPHA workers' sense of efficacy, nor is there an educational intervention designed specifically to bolster disaster recovery-phase efficacy perceptions. Here, we describe the important role of the LPHA workforce in disaster recovery and the operational- and efficacy-related research gaps inherent in today's disaster recovery practices. We then propose a behavioral framework that can be used to examine LPHA workers' disaster recovery perceptions and suggest a research agenda to enhance LPHA workforce disaster recovery efficacy through an evidence-informed educational intervention. ( Disaster Med Public Health Preparedness . 2015;9:403–408)